Characterization of finger millet global germplasm diversity panel for grain nutrients content for utilization in biofortification breeding - Backiyalakshmi, Chinnadurai; Babu, Chakrapani; Deshpande, Santosh; Govindaraj, Mahalingam; Gupta, Rajeev; Sudhagar, Rajaprakasam; Naresh, Dagunapur; Anitha, Seetha; Peerzada, Ovais; Sajja, Sobhan; Singh, Kuldeep; Vetriventhan, Mani (Crop Science Society of America, 2024)
Finger millet (Eleusine coracana L.) is a versatile dryland crop known for its high calcium (Ca) content. Estimating the variability for grain nutrients in diverse germplasm is important for developing biofortified cultivars. A finger millet diversity panel consisting of 310 accessions and four controls was evaluated in two rainy seasons at International Crops Research Institute for the Semi-Arid Tropics, Hyderabad, India, to assess variability for grain nutrient content and its association with agronomic traits and identify promising accessions. Inductively coupled plasma optical emission electrometry was used to analyze grain nutrients content, and the protein content was estimated from the total nitrogen content of the finger millet grains using the sulfuric acid–selenium digestion method. Highly significant variability was found for all the grain nutrients and was significantly influenced by the genotype, environment, and their interactions. Grain nutrients showed a significant relationship between the 2 years (R2 = 0.06 for phosphorus to 0.60 for Ca, p ≥ 0.001). A nonsignificant correlation between grain yield and Ca was noticed among accessions within landraces, breeding lines, and accessions from Asia, while this correlation was significantly negative among accessions from Africa and in the entire set. The estimated percent daily values indicated that the consumption of 100 g of finger millet grains could potentially contribute to the recommended dietary allowance of up to 49% Ca, 52% magnesium, 23% protein, 23% iron, and 26% zinc. This study provides valuable insights into the variability in the finger millet germplasm, and identified grain nutrient dense accessions, that could be used in finger millet improvement to develop the biofortified cultivars.